Monitoring the succession of bacterial communities during storage of raw meat - Doulgeraki, Agapi I. (Cranfield University, 2010)
Fresh meat is exposed to various factors which cause microbiological contamination during handling, processing, packaging and storage. Furthermore, the storage conditions applied may affect the microbial association of the product and consequently the spoilage process. Therefore, the purpose and importance of this study was to identify areas that should be addressed to monitor the succession of bacterial communities during storage of raw meat. The improvement of the microbiological quality and safety of meat was also studied. Cont/d.